Cost-effectiveness analysis of oral versus intravenous drip infusion of levofloxacin in the treatment of acute lower respiratory tract infection in Chinese elderly patients - Zhang L (Dove Medical Press, 2017)
Libin Zhang, Ping Hu Department of Pharmaceutics, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Yangpu, Shanghai, People’s Republic of China Aim: Pharmacoeconomic cost-effectiveness analysis of two different dosage regimens of levofloxacin in the treatment of acute lower respiratory tract infection in elderly patients. Methods: A total of 108 elderly patients with acute lower respiratory tract infection who visited by our hospital between September 2013 and September 2014 were randomly divided into Group A and Group B, with 54 patients in each group. In Group A, levofloxacin injection was given for continuous intravenous infusion treatment, whereas in Group B, levofloxacin injection and levofloxacin capsule were given as sequential therapy (ST). The period of treatment for both the groups was 10 days, and minimum cost analysis was used to analyze the treatment. Results: Groups A and B had cure rates of 61.1% and 59.3% (P>0.05), effective rates of 88.9% and 83.3% (P>0.05), bacterial clearance rates of 96.3% and 92.6% (P>0.05), and incidence rates of adverse reactions of 7.4% and 3.7% (P>0.05), respectively. Treatment costs of Groups A and B were 1,588 RMB and 1,150 RMB, respectively, whereas the cost-effectiveness of the two groups was at 17.86 and 13.81, respectively (P<0.05). Conclusion: Levofloxacin ST had relatively higher cost-effectiveness ratio for the treatment of acute lower respiratory tract infection in elderly patients, especially Chinese. Keywords: Pharmacoeconomic, cost-effectiveness, dosage, elderly patient, treatment cost, Chinese